Evaluation of General Characteristics of Local Isolates Helicobacter pylori Bacterium that Causing Acute and Hemorrhage Peptic Ulcer in Adults - Ali, Zanab Sami; Ahmed, Ali Shihab; Zbar, Nidhaal Sehail (Al-Nahrain Journal of Science, 2018)
This study was amid to isolate, identify and study the genomic profile of hemorrhage and acute peptic ulcer infections by Helicobacter pylori bacterium in patients at the age (40- 60 year). Two techniques for identification of the infection by H. pylori were used, invasive and non invasive. Blood and faeces specimens were examined directly in hospital for specific antibody and antigen detection. One hundred and twenty biopsies specimens were used for the fast urea tests and. A new medium (ZAN-1) was prepared also other types of media were modified to be suitable for bacterial growth and isolation. Virulent factors such as time of color change in the fast urea solution by urease activity and ammonia production were studied, also specific shape was determined by Scanning Electron Microscope (SEM). Other tests such as lecithinase test, oxidase, catalase and blood hemolysis were done for identification of this bacterium. Two isolates were selected to represent the hemorrhage and acute infections. Hemorrhage isolate exhibited different characters especially in blood hemolysis and lecithinase activity. Antimicrobial susceptibility test indicated that acute isolate is more resistant than hemorrhage. The results of genomic profile indicated the absence of the plasmids and the virulent factors were of chromosomal source.